Bioavailability and pharmacokinetics of cefotaxime in Muscovy ducks - Aboubakr, Mohamed (International Journal of Pharmacology and Toxicology, 2016)
The pharmacokinetic profile of cefotaxime following a single intravenous (IV) and intramuscular (IM) injection was studied in Muscovy ducks. Cefotaxime was given at a dose rate of 25 mg/kg b.wt. for both routes. After IV injection, the plasma levels of cefotaxime estimated at 0.08 h was 70.87 Î¼g/ml, which declined gradually and cefotaxime was detected up to 10 h (0.59 Î¼g/ml). The mean values of CL, Vdss and t1/2Î² of cefotaxime in muscovy ducks were 0.22 l/kg/h, 0.51 l/kg and 1.81 h, respectively. After IM injection, maximum plasma concentration (Cmax) was (14.72 Î¼g/ml), time of maximal plasma concentration (tmax) was (2.3 h) and elimination half-life (t1/2el)was (1.77 h). Bioavailability following IM injection was 79.61%, and in vitro protein binding percent was 31.48%. A recommended IM dosage for cefotaxime in muscovy ducks would be 30 mg/kg b.wt., repeated at 12 h intervals will provide a therapeutic plasma concentrations exceeding the MICâ‰¤0.5 Âµg/ml for most susceptible pathogens in ducks.